STRATEGIES FOR TRANSLATING NEOLOGISMS IN CONTEMPORARY SCIENCE FICTION: A LINGUISTIC ANALYSIS. ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Science fiction is a genre defined by "the literature of change," often requiring the creation of new words—neologisms—to describe futuristic technologies or alien concepts. This article explores the linguistic strategies used to translate these invented terms from English into target languages. It categorizes neologisms into types such as compound words, blends, and derived forms. By examining works like George Orwell’s 1984 and William Gibson’s Neuromancer, this study analyzes how translators use borrowing, transcription, and calque to maintain the "future-feel" of the text without confusing the reader. The research concludes that a balance between foreignization and domestication is essential for preserving the author's original vision.​